THE EFFECT OF FLOATING AQUAPONIC SYSTEM WITH DIFFERENT TYPES OF PLANTS ON THE NUTRITION OF TILAPIA (Oreochromis niloticus) MEAT - Djonu, Asriati; Salosso, Yuliana; Jasmanindar, Yudiana; Santoso, Priyo (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2025)
The floating aquaponic system using different types of plants can be an environmentally friendly cultivation solution, easy to apply on a household scale and profitable. However, various types of plants in aquaponics have different nutrient absorption capacities that can affect the quality of fish meat. This research aimed to see the type of plant that is best at producing quality of tilapia (Oreochromis niloticus) meat produced from cultivation with a floating aquaponic system using different types of plants. The types of plants used included spinach (Ipomoea aquatica), pakcoy (Brassica rapa), lettuce (Lactuca sativa), and control (without plants), which were repeated three times. Experimental method is used in this research. The results showed that the best treatment was I. aquatica plant treatment which produced a dry weight of tilapia meat of 19.608%; protein of 61.575% DW (Dry Weight); fat of 3.586% DW and ash content of 8.239% DW. The results showed that using I. aquatica plants produced better meat quality than the other two plants. Compared to the control treatment, the difference was very significant. This method has the potential to be widely applied at the household scale in urban and semi-urban areas to get a source of nutritious animal protein and vegetables with minimal use of land, facilities and water.